2021
DOI: 10.3758/s13423-021-01908-x
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in sustained attention tasks: A meta-analysis

Abstract: Many aspects of attention decline with aging. There is a current debate on how aging also affects sustained attention. In this study, we contribute to this debate by meta-analytically comparing performance on the go/no-go Sustained Attention to Response Task (SART) in younger and older adults. We included only studies in which the SART had a low proportion of no-go trials (5%–30%), there was a random or quasirandom stimulus presentation, and data on both healthy younger and older adults were available. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 106 publications
(320 reference statements)
11
38
0
Order By: Relevance
“…Collectively the data were most consistent with the hypothesized pattern of results in Figure 1B (speed difference + better sustained attention). The data were also consistent with prior work showing similar patterns in both traditional vigilance tasks (Tomporowski & Tinsley, 1996), and go/no-go tasks like the SART (Brache et al, 2010;Staub et al, 2014aStaub et al, , 2014cStaub et al, , 2015Vallesi et al, 2021). The present results cannot resolve the discrepancies observed between go/no-go tasks and other cognitive control tasks.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Collectively the data were most consistent with the hypothesized pattern of results in Figure 1B (speed difference + better sustained attention). The data were also consistent with prior work showing similar patterns in both traditional vigilance tasks (Tomporowski & Tinsley, 1996), and go/no-go tasks like the SART (Brache et al, 2010;Staub et al, 2014aStaub et al, , 2014cStaub et al, , 2015Vallesi et al, 2021). The present results cannot resolve the discrepancies observed between go/no-go tasks and other cognitive control tasks.…”
Section: Discussionsupporting
confidence: 91%
“…The present results cannot resolve the discrepancies observed between go/no-go tasks and other cognitive control tasks. That is, older adults tend to show more Stroop interference and reduced proactive control in continuous performance tasks, (e.g, AX-CPT; Braver, Satpute, Rush, Racine, & Barch, 2005;Bugg, 2014a;Paxton et al, 2006;Vallesi et al, 2021), but they show fewer no-go errors in the SART (Vallesi et al, 2021). We used the PVT specifically because it does not involve resolving conflict or inhibiting a prepotent response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, deficits in sustained attention are likely to be a contributing factor to the impaired proactive control of stroke patients. However, previous studies indicated that motivation, fatigue, and mind wandering might have a negative effect on sustained attention for elderly people ( 29 ). Proactive control generally requires more effort, subsequently leads to more fatigue, which is most likely associated with the tendency to favor reactive over proactive control.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, many studies provided evidence for an age‐related decline in executive functions, among other domains, showing that healthy older adults perform poorer than the younger counterparts on executive function tasks documenting for instance working memory deficits, reduced inhibitory control, and decreased task‐switching ability (MacPherson et al., 2015 ; West, 1996 ; Zanto & Gazzaley, 2019 ; but see Vallesi et al., 2021 ). As EEG‐NFT could be a potentially effective method to counteract this age‐related executive function decline, we assessed whether, to date, studies have provided reliable evidence for its effectiveness.…”
Section: Introductionmentioning
confidence: 99%